KOMPETENSI GURU BK DALAM PENINGKATAN PELAYANAN BIMBINGAN KONSELING DI SMK NEGERI 1 DOLOK MERAWAN - Pebrina Lasambouw (Al-Mursyid : Jurnal Ikatan Alumni Bimbingan dan Konseling Islam (IKABKI), 2020)
This research was conducted at SMK Negeri 1 Dolok Merawan, while the aim was to 1) describe how the competence of counseling teachers at SMK Negeri 1 Dolok Merawan 2) describe how counseling guidance services at SMK Negeri 1 Dolok Merawan 3) describe how counseling guidance services at SMK Negeri 1 1 Dolok Merawan. The subjects in this study were the principal, homeroom teacher, BK teacher and students of SMK Negeri 1 Dolok Merawan. This type of research is a qualitative study that describes how the competence of BK teachers in SMK Negeri 1 Dolok Merawan. Data collection techniques in this study were observation, interviews, and documentation studies. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. After conducting the research, the results show that: BK teacher competence in SMK Negeri 1 Dolok Merawan is quite good. The competence of good competent BK BK 1 BK vocational school teachers has an impact on increasing the guidance of counseling guidance. Finally, an atmosphere of orderly and conducive teaching and learning is created and students' achievement is increased.Keywords: Competence, Guidance Counseling, Counseling Guidance Services